2014
DOI: 10.1016/j.solener.2014.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Optical cavity for improved performance of solar receivers in solar-thermal systems

Abstract: Abstract:A principal loss mechanism for solar receivers in solar-thermal systems is radiation from the absorbing surface. This loss can be reduced by using the concept of directional selectivity in which radiation is suppressed at angles larger than the incident angle of the sunlight striking the absorber. Directional selectivity can achieve efficiencies similar to high solar concentration, without the drawbacks associated with large heat fluxes. A specularly reflective hemispherical cavity placed over the abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 29 publications
(37 reference statements)
2
23
0
Order By: Relevance
“…1. Similar cavities have been shown to reduce radiative recombination emission losses in PV cells [21] and thermal emission losses in thermal systems [22,23]. Here, we show how it can also increase absorption in thin film PV cells.…”
Section: Hemi-ellipsoidal Optical Cavitysupporting
confidence: 56%
“…1. Similar cavities have been shown to reduce radiative recombination emission losses in PV cells [21] and thermal emission losses in thermal systems [22,23]. Here, we show how it can also increase absorption in thin film PV cells.…”
Section: Hemi-ellipsoidal Optical Cavitysupporting
confidence: 56%
“…The results showed that some improvement on the optical efficiency can be done during changing the dimensions of the interior vortex shape which can covered the dead area of the studied receiver. Enhancing the thermal performance of solar receiver through the focusing on the optical characteristics was tried by Weinstein et al [32]. In their research they tried to decrease the thermal losses, especially the radiative one, by applying the directional selectivity idea which leads to a reduction in the mentioned heat loss by 75% and as a result reaching high receiver efficiency for solar thermal applications.…”
mentioning
confidence: 99%
“…Several possible approaches to achieve thermal emission with angular selectivity are illustrated in Figure 5. The first approach shown in Figure 5a is based on a reflective cavity with an aperture [142][143][144]. Thermally emitted photons propagating in the direction close to the normal to the emitter surface escape the cavity through the aperture.…”
Section: Selective Surfaces For Solar Thermal Energy Generationmentioning
confidence: 99%